Uma análise do fenômeno Booktok na promoção de letramentos literário e digital, a partir da obra “Dom Casmurro”, de Machado de Assis - França, Nílio Rodrigues de (2024)
This research is linked to the Language and Social Practices research line of the Interdisciplinary Postgraduate Program in Education, Language, and Technologies (PPG-IELT) at the State University of Goiás (UEG). Its theme is incorporating information and communication technologies into social reading practices in the context of digital culture, shaped by cultural, social, and technological transformations. Therefore, the research aims to answer the following question: What strategies have been developed in the BookTok community to train cyber-readers in the work Dom Casmurro by Machado de Assis? Thus, as a general objective, the research aims to understand the strategies developed by Booktokers in the BookTok community for forming cyber-readers of Machado de Assis' Dom Casmurro and how these strategies are articulated with literary and digital literacy practices. To this end, it is necessary to analyze how the new generations relate to classic literature and how digital platforms can promote literary literacy in contemporary interconnected society. Exploring this intersection between literacy, literature, and technology is hoped to provide insights into the debate on the importance of reading in today's society and how new forms of digital literacy can contribute to forming more critical and engaged readers. To this end, it investigates how reading in contemporary society has been carried out in digital media, especially in the context of literary literacy in digital environments, with a focus on the Booktok phenomenon, the TikTok app, and its relationship with Machado de Assis' Dom Casmurro. The theoretical basis goes through concepts related to reading in physical and digital media, observing literacy practices, and focusing above all on the theoretical perspectives for cyberliterature of Santaella (2021; 2013; 2012; 2010; 2004), Lévy (1999), Castells (1999), Kenski (2012) and Jenkins (2013). Concerning literary literacy, the research uses Cosson (2022; 2021b), Soares (2023; 2009; 2004; 1985), and Paulino (2010). As for digital literacy: Coscarelli (2021; 2016), Coscarelli e Ribeiro (2005), Ribeiro e Coscarelli (2017), Ribeiro (2023a), Kersch, Coscarelli and Cani (2016), Dudeney, Hockly and Pegrum (2016), Kalantziz, Cope and Pinheiro (2022), Rojo and Moura (2012) and Xavier and Marcuschi (2010). Finally, Fischer (2006), Freire (1989), Lajolo, Zilberman (1019) and Martins (2012a) are used to discuss reading in different media, and Nunes (2018) discuss reading in the digital age. We also used Gerhardt and Behling (2014), Orlandi (2022), Musso (2015), and Stokel- Walker (2022) to discuss social networks. In terms of methodology, this is an exploratory study based on qualitative bibliographical research developed using netnographic research. The corpus of study used in the analysis was the @patzzic profile of the BookTok literary community, which promotes literary works on the TikTok social network. The research shows that, throughout history, reading practices have undergone countless transformations, not only in how books are produced and consumed but also in how people appropriate texts, influenced by the advance of digital culture. These changes, for example, have transformed how people read, write, articulate, and interact with information, impacting how language is used and understood in different social spheres. Given this, because of the analysis of the interactions, it is possible to see that the direct influence of Booktokers has significantly shaped the stimulus to reading and, consequently, the formation of cyber-readers.